Epileptiform activity in alcohol dependent patients and possibilities of its indirect measurement - Bob, Petr; Jasova, Denisa; Bízik, Gustáv; Raboch, Jiri (PLoS One, 2011)
BACKGROUND: Alcohol dependence during withdrawal and also in abstinent period in many cases is related to reduced inhibitory functions and kindling that may appear in the form of psychosensory symptoms similar to temporal lobe epilepsy frequently in conditions of normal EEG and without seizures. Because temporal lobe epileptic activity tend to spread between hemispheres, it is possible to suppose that measures reflecting interhemispheric information transfer such as electrodermal activity (EDA) might be related to the psychosensory symptoms. METHODS AND FINDINGS: We have performed measurement of bilateral EDA, psychosensory symptoms (LSCL-33) and alcohol craving (ACQ) in 34 alcohol dependent patients and 32 healthy controls. The results in alcohol dependent patients show that during rest conditions the psychosensory symptoms (LSCL-33) are related to EDA transinformation (PTI) between left and right EDA records (Spearman r = 0.44, p<0.01). CONCLUSIONS: The result may present potentially useful clinical finding suggesting a possibility to indirectly assess epileptiform changes in alcohol dependent patients.
Keywords: dospělí; Galvanic Skin Response; Middle Aged; Alcoholism; lidé středního věku; Epilepsy; lidé; Female; epilepsie; alkoholismus; mužské pohlaví; Male; galvanická kožní odpověď; Adult; ženské pohlaví; Humans